Medición y evaluación en comunicación estratégica: Caso de estudio Yanbal Ecuador. - Galarza Alvear, Sofía Elizabeth (2014)
This research focuses on the measurement and evaluation of strategic communication planning and main objective is to analyze the actions and goals of communication of Yanbal Ecuador in the year 2013 and identify if they are aligned with the overall strategic planning of the organization. The methodology used in the research was a structured interview semi Comunication Management Brigde made model-based Enterprise Communications Manager, as well as also the documentary analysis of the sustainability and corporate responsibility report and the Business Plan of communication 2012-2013 Yanbal Ecuador. Through this research it was found that the organizational objectives of the company in 2013 were linked with the objectives of the communication of the same year, also Yanbal Communications Department works with tools, strategies and execute specific actions in terms of strategic communication planning and measurement and evaluation function is located within these.